Salmonella Typhi-specific multifunctional CD8+ T cells play a dominant role in protection from typhoid fever in humans. Issue 1 (December 2016) - Fresnay, Stephanie; McArthur, Monica; Magder, Laurence; Darton, Thomas; Jones, Claire; Waddington, Claire; Blohmke, Christoph; Angus, Brian; Levine, Myron; Pollard, Andrew; Sztein, Marcelo
Abstract Background Typhoid fever, caused by the human-restricted organismSalmonella Typhi (S. Typhi), is a major public health problem worldwide. Development of novel vaccines remains imperative, but is hampered by an incomplete understanding of the immune responses that correlate with protection. Methods Recently, a controlled human infection model was re-established in which volunteers received 103 cfu wild-typeS. Typhi (Quailes strain) orally. Twenty-one volunteers were evaluated for their cell-mediated immune (CMI) responses. Ex vivo PBMC isolated before and up to 1 year after challenge were exposed to threeS. Typhi-infected targets, i.e., autologous B lymphoblastoid cell-lines (B-LCL), autologous blasts and HLA-E restricted AEH B-LCL cells. CMI responses were evaluated using 14-color multiparametric flow cytometry to detect simultaneously five intracellular cytokines/chemokines (i.e., IL-17A, IL-2, IFN-g, TNF-a and MIP-1b) and a marker of degranulation/cytotoxic activity (CD107a). Results Herein we provide the first evidence thatS. Typhi-specific CD8+ responses correlate with clinical outcome in humans challenged with wild-typeS. Typhi. Higher multifunctionalS. Typhi-specific CD8+ baseline responses were associated with protection against typhoid and delayed disease onset. Moreover, following challenge, development of typhoid fever was accompanied by decreases in circulatingS. Typhi-specific CD8+ T effector/memory (TEM ) with gut homing potential, suggesting migration to the site(s) of infection. In contrast, protection against disease was associated with low or no changes in circulatingS . Typhi-specific TEM . Conclusions These studies provide novel insights into the protective immune responses against typhoid disease that will aid in selection and development of new vaccine candidates.